Role of granular activated carbon in the microalgal cultivation from bacteria contamination. (January 2018) - Ni, Zhi-Yi; Li, Jing-Ya; Xiong, Zhao-Zhao; Cheng, Li-Hua; Xu, Xin-Hua
Graphical abstract: Highlights: GAC addition could avoid the decline of microalgae growth caused by bacteria. GAC could adsorb bacteria and its EOM to mitigate bacterial contamination. GAC addition could greatly reduce the bioavailability of EOM. Abstract: Microalgal wastewater treatment has been considered as one of the most promising measures to treat nitrogen and phosphorus in the municipal wastewater. While the municipal wastewater provides sufficient nitrogen and phosphorus for microalgal growth, the microalgae still faces serious biological contamination caused by bacteria in wastewater. In this study, the commercial granular activated carbon (GAC) was added into the simulated municipal wastewater to avoid the influence of bacteria on the growth of microalgae. The extracellular organic matter (EOM) in microalgal broth was then characterized to enlighten the role of GAC in reducing the bioavailability of EOM. The results showed that the GAC addition could increase the dry weight of microalgae from 0.06 mg L −1 to 0.46 mg L −1 under the condition of bacterial inoculation. The GAC could mitigate bacterial contamination mainly due to its adsorption of both bacteria and EOM that might contain algicidal extracellular substances. Moreover, compared to the control group, the GAC addition could mitigate the microalgal lysis caused by bacteria and thus greatly reduce the bioavailability of EOM from 2.80 mg L −1 to 0.61 mg L −1, which was beneficial for the improvement of biostability and reuse of effluent after the microalgal harvesting.